The Effectiveness of Training: Exploring the Influence of Learning Technology, Motivation, and Participant Satisfaction - Sardo, Sardo; Parwoto, Parwoto (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2024)
Employee education and development are key elements to achieving competitive advantage in the ever-changing business era. This study investigates the impact of learning technology on various aspects of training, including participant satisfaction, motivation, and overall training effectiveness. Seven hypotheses examine different relationships and mediation effects within this context. Findings reveal that learning technology positively influences training satisfaction, motivation, and effectiveness. Key indicators include social support and personal development, highlighting their significant roles in enhancing these outcomes. Management implications suggest increased investment in learning technologies, continuous evaluation, and adaptive strategies to optimize training results. The study underscores the importance of interactive and engaging technology in improving training programs.